Switching algorithm for single Z-source boost multilevel inverter with ability of voltage control - Banaei, Mohamad Reza; Dehghanzadeh, Ali Reza; Fazel, Ali; Oskouei, Aida Baghbany (IET power electronics, 2013)
This study proposes a new topology of cascaded transformer-based multilevel inverter using single Z-source. The suggested circuit consists of only one Z network and one DC voltage source; as a result installation area is reduced. In this topology, the output voltage amplitude is not limited to DC voltage source similar to traditional cascaded transformer-based multilevel inverter and can be increased with Z network shoot-through state control flexibly. Besides, the same as traditional Z-source inverter, it is more reliable against short circuit. Also, a particular switching algorithm has been suggested for presented inverter, which can obtain total harmonic distortion (THD) of output voltage nearly constant for different boost ratio. Moreover, as compared to traditional Z-source inverter, the THD of output voltage is decreased in the suggested topology. The performance of proposed inverter and switching algorithm are validated with simulation results using MATLAB/SIMULINK software and experimental results based PCI-1716 data acquisition system.